2007
DOI: 10.1590/s0102-86502007000200003
|View full text |Cite
|
Sign up to set email alerts
|

Bone tissue microscopic findings related to the use of diode laser (830etam) in ovine mandible submitted to distraction osteogenesis

Abstract: Purpose: To analyze the microscopic characteristics of the effect of Gallium-Aluminum Arsenid diode laser (GaAlAs830ηm) applied during the activation and consolidation period to ovine mandibles submitted to distraction osteogenesis. Methods: Eighteen sheep underwent surgery in order to have bone distractors implanted in the left side of the jaw area. They were divided into three groups: 1 -Control; 2 -Laser irradiation during the activation period; 3 -Laser irradiation during the fixation period. The irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 18 publications
5
18
0
7
Order By: Relevance
“…On the other hand, when applied during the latency and activation period, laser therapy caused a decrease in hardness and modulus of elasticity values, with a consequent delay in bone calcification. The results obtained in sheep D (LLLT applied during the bone consolidation period), namely hardness of 414.4 MPa and modulus of elasticity of 12.3 GPa (Table 1), are compatible with the results described by Cerqueira et al (18) and Kreisner et al (19), who also reported positive results in terms of bone regeneration and new bone formation in mandibles submitted to distraction osteogenesis and LLLT in the bone consolidation period. Sheep E (control) was not submitted to LLLT.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, when applied during the latency and activation period, laser therapy caused a decrease in hardness and modulus of elasticity values, with a consequent delay in bone calcification. The results obtained in sheep D (LLLT applied during the bone consolidation period), namely hardness of 414.4 MPa and modulus of elasticity of 12.3 GPa (Table 1), are compatible with the results described by Cerqueira et al (18) and Kreisner et al (19), who also reported positive results in terms of bone regeneration and new bone formation in mandibles submitted to distraction osteogenesis and LLLT in the bone consolidation period. Sheep E (control) was not submitted to LLLT.…”
Section: Discussionsupporting
confidence: 90%
“…The lowest modulus of elasticity and hardness results were found in sheep C, which used the distractor for 33 days and was submitted to LLLT in the activation period. These findings may suggest that the application of LLLT during the activation period in fact provokes a delay in bone healing, a hypothesis that is reinforced by the marked presence of cartilage tissue and endochondral ossification observed in specimens irradiated with LLLT during the activation period, as proposed by Cerqueira et al (18). Although the use of distraction osteogenesis has become increasingly common, it can cause significant discomfort to the patient, especially when external devices are used, possibly leading to infections, paresthesia, hypertrophic scars and social difficulties (14).…”
Section: Discussionsupporting
confidence: 55%
“…LLLT is among the techniques used to facilitate the recovery process in bone tissue during recent years. Conducted studies analyzed the therapeutic action of LLLT in the first connective tissue and it was determined that in time LLLT reduced inflammation, stimulated fibroblast proliferation and collagen production, increased local micro-vascularization and bone mineralization, and implant osteointegration by stimulating osteoblastic activity, and it was proven that these properties of laser had positive effects on bone recovery (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…Son zamanlardaki birçok çalışmada da DDLT'nin kemik oluşu-munu uyarıcı etkileri üzerine çalışmalar devam etmektedir. Yapılmış araştırmalar DDLT'nin kemik mineralizasyonunda ve osteoblast hücrelerin sayılarında arttırıcı etkisini göstermektedir (68)(69)(70)(71). DDLT'nin diş çekiminden sonra alveolar tamirde önemli rol aldığı, osteoblast kültürle-rinde, çoğalma, farklılaşma ve kalsifikasyon sürecini etkilediği gösterilmiştir (72).…”
Section: Kemik İyileşmesi Ve Rejenerasyonunda Ddltunclassified